Optimizing Semiconductor Packaging Operations Through Business Intelligence: A Collaborative Approach for Skill Development in India - Mohan, Chetna (Digital Repository of Theses - SSBM Geneva, 2025)
This study aims to identify and examine the critical business skills necessary for success in the ever-evolving field of semiconductor manufacturing in packaging. This study explores the important business and technical skills needed for success in the fast-changing field of semiconductor manufacturing, with a focus on packaging operations in India. As Industry 4.0 continues to impact the manufacturing sector, companies must combine technical know-how with strong business decision-making. The research examines how tools like Business Intelligence (BI) and Big Data Analysis (BDA) can help improve processes by collecting real-time data, reducing production defects and improving product quality. The Indian semiconductor packaging industry is growing quickly and faces the challenge of keeping up with global standards. As Industry 4.0 technologies transform manufacturing, combining technical expertise with strong business decision-making has become essential. Surveys and questionnaires were distributed to professionals in the semiconductor packaging sector to gather data on current skill levels, training needs and adoption of Industry 4.0 technologies. Combining open-ended and close-ended questions helped capture numerical data and detailed opinions. The study also highlights the role of Industry 4.0 technologies, such as IIoT with Artificial Intelligence (AI), Machine Learning (ML) and automation, in making manufacturing smarter and more efficient for better data handling, smarter decision-making and fewer errors in production. A significant focus of the research is the need for workforce training. Employees need the right skills to use new systems and tools effectively, so companies must invest in training programs focusing on digital skills and data use. In addition, the thesis underlines the importance of collaboration between industry and academic institutions, which can help develop skilled talent, drive innovation and support the digital transformation of India’s semiconductor sector. Overall, this research provides practical insights and a future-ready plan for improving backend semiconductor packaging operations by aligning it with technology adoption, skill development and strategic planning. The study offers a clear path toward long-term growth and global competitiveness for India’s semiconductor industry. Keywords: Smart manufacturing, operations, skill development, semiconductor packaging, India, Industry 4.0, business skills, business intelligence